1993
DOI: 10.1038/bjc.1993.176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reconstituted basement membrane components on the growth of a panel of human tumour cell lines in nude mice

Abstract: Sunmmary Previous reports have indicated that reconstituted basement membrane (matrigel), when co-injected with either established or primary human tumour cells, can improve the growth of subcutaneous xenografts in nude mice. The human adenocarcinoma cell lines A549, SW480, and WiDr, and the human fibrosarcoma cell line HT1080scc2 exhibit varying degrees of tumourigenicity in nude mice. All these lines showed increased tumourigenicity and/or growth rate, together with a change towards a more differentiated tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…A number of articles have shown that matrigel can help to establish xenografts from a variety of cell lines [Topley et al, 1993].…”
Section: Discussionmentioning
confidence: 99%
“…A number of articles have shown that matrigel can help to establish xenografts from a variety of cell lines [Topley et al, 1993].…”
Section: Discussionmentioning
confidence: 99%
“…Matrigel is a mixture of laminin, collagen IV, heparan sulfate, and entactin that creates a nutrientrich environment to promote rapid tumor growth, resulting in palpable tumors within 4-5 wk after cell implantation (48,49). Tumors were allowed to grow to a mean volume of approximately $50 mm 3 before initiation of treatment with RL4B TCRm or isotype control Ab (Fig.…”
Section: Rl4b Tcrm Is Effective In Vivo In An Orthotopic Breast Cancementioning
confidence: 99%
“…In particular, it was shown that coinjection of purified laminin-1 and of lung or colon cancer cells increases the growth of the tumors developed as xenografts in nude mice; such an effect was not observed when collagen IV, another basement membrane molecule, was used. 17,18 It was postulated that the increase in tumor growth resulted from the improved growth conditions brought by laminin-1, 17 while other authors showed that the interaction of the laminin-containing Matrigel with human colon adenocarcinoma cells allows the selection of a subset of neoplastic cells that display tumorigenic potential by themselves even in the absence of Matrigel. 19 The mechanisms through which laminin-1 exerts its effect remain unclear.…”
mentioning
confidence: 99%